Condiciones de omnicanalidad en un sector empresarial de Colombia - Marisol Valencia Cárdenas; Liliana Cárdenas Cano; María Eugenia Jiménez Ruiz; Luder Estefanny Velandia Estrada; Mayerlin Roldán Sepúlveda (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The purpose of the research is to inquire about the fulfillment of omnichannel conditions in consumers and micro-businesses of the processed food sector in the metropolitan area of Medellin, Colombia, from the study of the fulfillment of conditions linked to three components: sales channels, marketing models and the supply chain, with the transversality of digitization. For this purpose, we used a complementary research methodology, the first method is quantitative, applying a survey instrument to consumers, related to omnichannel conditions; the second is qualitative, with a descriptive and non-experimental approach analyzing five (5) case studies of micro-businesses. Among the main results is that microbusinesses are not 100 % omnichannel, but multichannel is known, that is not the same, but it is part of it, and data storage is perceived positively, in addition, consumers are not omnichannel and also, do not know various concepts of digital integration of this strategy; nevertheless, consumers perceive that the analytics of the data provided and its integration can improve the perception of benefits, incentives and customer satisfaction, promoting loyalty and growth of microbusinesses.
Keywords: M31; O3; M1; 330; Marketing; innovation; business management